Evidence of directed interactions between individuals in captive flamingo flocks - Rose, Paul E.; Croft, Darren P. (Wildfowl, 2015)
Information on social behaviour traits can be inferred from observed associations or measured as the frequency of direct interactions between individuals. For some species, information on interactions between individuals, and the form that these interactions take, is limited. This paper describes three social interactions (affiliative, mate-guarding and directed aggression) seen in captive flamingos (Phoenicoparrus sp. and Phoenicopterus sp.) that could be of help to those studying flamingo social behaviour, by adding explanation of direct interactions to the overall flamingo ethogram. Information on how flamingos organise their social structure appears infrequently in the literature, and what (if any) specific social interactions are performed from one bird to another can be lacking in description and definition. The behaviours explained in this paper provide an insight into the social lives of flamingos that can give support to further, deeper, studies into social hierarchy and social affiliation.